WAWASAN AL-QUR’AN TENTANG SYURA DAN DEMOKRASI - Mustaqim, Abdul (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2018)
The recent discourse on democracy has become increasingly widespread. This is evident from the stage of contemporary politics, where Islamic movements are increasingly involved in issues of democratization and civil society. Meanwhile, there are still many parties who question whether the teachings of the Quran and the values of democracy can be harmonious and compatible. There is even a claim that the definition of democracy is often formulated narrowly from a Western point of view alone.The problem is that if democracy is viewed in accordance with the teachings of Islam, why do most of the Muslim countries do not choose their system of government based on democracy? Is not this an attitude of ambivalence?This paper tries to elaborate critically on the basic principles of Islam in governing the system of government, and then compare with the basic principles that exist in the concept of democracyKeywords: Qur’an, Sura and Democracy